An Analysis on The Use of Slang in Mean Girls Movie: Key words: Sociolinguistics, language, and slang - Oktaviani, Ni Wayan; singkoh, Olga; olii, Sanerita T. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The goal of the study is to identify the different slang terms that the performers in the Signify Girls movie used as well as explain what such terms mean. This study's research strategy might be characterized as a setting for gathering and analyzing information from the Mean Girls movie. The writer has the correct solution for analyzing the issue in the Mean Girls movie when employing qualitative research in place of descriptive data such as written and spoken. This study used the Eric Partridge theory to classify the slang terms that the actors in the Mean Girls movie used the most, and the Holmes (2013) theory of social factors that are the conversation's subject, setting, and participants' social relationships was used to analyze the context of the words used. The total number of words gleaned from the Mean Girls movie, including phrases, is 7. The top seven slang phrases used by actors are all listed here. Of the seven slang terms, three are classified as "society slang," two as "public house slang," and two as "slang at public schools and universities." The seven slang phrases spoken by the characters all have different context-specific meanings despite being the same. The conversation that is currently taking place is greatly influenced by the conversation's topic, location, and social relationships with the group. The author offers advice to the following researcher on how to enhance sociolinguistic analysis by carrying out comparable studies with diverse research subjects. The author cautions upcoming researchers to exercise caution when gathering slang word data because there are numerous comparable slang words with various meanings, depending on the conversational setting.